The causes of social stratification in Kiley Reid’s Such a Fun Age - Pragita, Bryan; Prasaja, Yoseph Bavo Agung (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This thesis examined the representation of social stratification in Kiley Reid's Such a Fun Age. It was based on the phenomenon of social inequality that continues to be relevant in contemporary society, which triggered the researcher's interest in how social stratification is manifested and perpetuated. The selection of this novel was based on its detailed depiction of complex power relations and disparities in access to resources between social classes. This study used Max Weber's multidimensional social stratification theory as the main framework, which involved the analysis of class, status, and power dimensions. The thesis researcher adopted a qualitative method with a descriptive-analytical design and close reading techniques. Textual data from the novel was collected and analyzed to identify the forms, causes, and impacts of social stratification experienced by the characters Emira from the lower class, Kelley from the middle class, and Alix from the upper class. The findings of the analysis showed that social stratification in this novel was manifested through significant differences in economic conditions, social prestige, and control over resources, which led to inequality of opportunity and discrimination. The main causes included inherited wealth, differences in access to education and employment, and the use of power by the dominant strata. The impact was seen in Emira's vulnerability to discrimination and limited access, in contrast to Alix's extensive privilege and control. This study concluded that the novel Such a Fun Age effectively reflected the complex structure of social stratification and emphasized the role of literature as a reflection of social reality.